FROM RESOURCE EXTRACTION TO INDUSTRIAL VALUE CREATION IN UZBEKISTAN’S MINING SECTOR - Kurbanova Mehriniso Nematjanovna (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2026)
This thesis examines the transition of Uzbekistan’s mining sector from resource extraction to industrial value creation. The study argues that mining competitiveness should no longer be measured only by extraction volume or export of raw materials, but by the capacity to create higher added value through deep processing, localization, resource efficiency, technological modernization and industrial cooperation. Using the case logic of a large mining and metallurgical enterprise, the thesis shows that energy saving, green technologies and local production linkages can transform mining from a raw-material sector into a strategic industrial platform. The findings suggest that Uzbekistan’s mining policy should prioritize value-added production, resource productivity and technological independence.